Truncus arteriosus: A method for correcting right pulmonary artery stenosis created by pulmonary artery banding - Stewart, Scott (1980)
Pulmonary artery banding can produce significant distortion of the branch pulmonary arteries including selective stenosis of one artery and only minor narrowing of the other. This may complicate total repair of the underlying anomaly. A successful technique is described for revising a severely stenotic orifice of the right pulmonary artery in truncus arteriosus.